Comparison between Brain Computed Tomography Scan and Transcranial Sonography to Evaluate Third Ventricle Width, Peri-Mesencephalic Cistern, and Sylvian Fissure in Traumatic Brain-Injured Patients - Oliveira, Raphael A. G.; de Oliveira Lima, Marcelo; Paiva, Wellingson Silva; de Sá Malbouisson, Luiz Marcelo; Teixeira, Manuel Jacobsen; Bor-Seng-Shu, Edson (Frontiers in Neurology, 2017)
Introduction: Transcranial color-coded duplex sonography (TCCS) may help guide multimodal monitoring in the neurocritical setting. It may provide indirect information about intracranial hypertension, such as midline shift, third ventricle width and peri-mesencephalic cistern obliteration. We aim to assess the agreement between brain computed tomography scan (CT scan) and TCCS in traumatic brain injury (TBI) patients. Methods: In this retrospective cross-sectional observational study, TCCS was performed within six hours before a brain CT scan. Only the first CT and TCCS after ICU admission were included. The agreement between the CT scan and TCCS was assessed by Bland-Altman plots and evaluating the intraclass correlation coefficient. Results: Overall, 15 consecutive patients were included (80% male, 42 ± 23 years of age, Glasgow Coma Score 5 [4,6]). The mean difference between the brain CT scan and TCCS in measuring the midline shift was 0.30 ± 2.1 mm (intraclass correlation coefficient: 0.93; p<0.01). An excellent correlation was also observed between the methods in assessing the third ventricle width (intraclass correlation coefficient: 0.88; p<0.01). Bland-Altman plots did not show any systematic bias in either agreement analysis. TCCS showed good accuracy in predicting non-compressed peri-mesencephalic cisterns (AUC: 0.83, 95% CI 0.46 to 1.0) and the presence of the Sylvian fissure (AUC: 0.91, 95% CI 0.73 to 1.0) on CT scan. Conclusions: TCCS is a promising tool and may be an alternative to CT scans for evaluating TBI patients.